Integrating care: the work of diabetes care technicians in an integrated care initiative - Christopher Bunn; Elissa Harwood; Kalsoom Akhter; David Simmons (BMC, 2020)
Abstract Background As diabetes prevalence rises world-wide, the arrangement of clinics and care packages is increasingly debated by health care professionals (HCPs), health service researchers, patient groups and policy makers. 'Integrated care', while representing a range of approaches, has been positioned as a promising solution with potential to benefit patients and health systems. This is particularly the case in rural populations which are often removed from centres of specialist care. The social arrangements within diabetes integrated care initiatives are understudied but are of particular importance to those implementing such initiatives. In this paper we explore the 'work' of integration through an analysis of the role played by Health Care Assistants (HCAs) who were specially trained in aspects of diabetes care and given the title 'Diabetes Care Technician' (DCT). Methods Using thematic analysis of interview (n = 55) and observation data (n = 40), we look at: how the role of DCTs was understood by patients and other HCPs, as well as the DCTs; and explore what DCTs did within the integrated care initiative. Results Our findings suggested that the DCTs saw their role as part of a hierarchy, providing links between members of the integrated team, and explaining and validating clinical decisions. Patients characterised DCTs as friends and advisors who provided continuity. Other HCPs perceived the DCTs as supportive, providing long-term monitoring and doing a different job to conventional HCAs. We found that DCTs had to navigate local terrain (social, ethical and physical), engage in significant conversation and negotiate treatment plans created through integrated care. The analysis suggests that relationships between patients and the DCTs were strong, had the quality of friendship and mitigated loneliness. Conclusions DCTs played multidimensional roles in the integrated care initiative that required great social and emotional skill. Building friendships with patients was central to their work, which mitigated loneliness and facilitated the care they provided.